Multiphase Flow Simulation in Heterogeneous Porous Media using a Hybrid FVM-FEM Scheme - Wendland, E.; Flensberg, D. (Trends in Computational and Applied Mathematics, 2003)
This work describes a numerical scheme for simulation of two-phase flow in heterogeneous porous media. The system of governing equations is transformed into an equivalent problem, as proposed by Peaceman (1977).